2017
DOI: 10.2106/jbjs.16.00230
|View full text |Cite
|
Sign up to set email alerts
|

Role of Weekly Teriparatide Administration in Osseous Union Enhancement within Six Months After Posterior or Transforaminal Lumbar Interbody Fusion for Osteoporosis-Associated Lumbar Degenerative Disorders

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 28 publications
0
93
0
Order By: Relevance
“…After removing 87 duplications from the 383 references, titles and abstracts of the remaining 296 references were reviewed for eligibility. Then, 12 references from three prospective comparative studies and eight randomized clinical trials were eligible for the comprehensive synthesis ( Fig 1) [ [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…After removing 87 duplications from the 383 references, titles and abstracts of the remaining 296 references were reviewed for eligibility. Then, 12 references from three prospective comparative studies and eight randomized clinical trials were eligible for the comprehensive synthesis ( Fig 1) [ [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…Cho et al [79] compared the effect of PTH1-34 and bisphosphonate administration on posterior lumbar interbody fusion in patients with osteoporosis through a prospective cohort study and concluded that there was no significant improvement in the overall fusion rate at 24 months after surgery and clinical outcome between the two groups, although the PTH1-34 group showed faster bony union than the bisphosphonate group. Ebata et al [80] reported that bone fusion, evaluated on CT images, after posterior or transforaminal lumbar interbody fusion in patients with osteoporosis was significantly higher in patients using PTH1-34 than the no PTH1-34 group, both at 4 and 6 months postoperatively. Although the positive effect of PTH1-34 on bone fusion has been described in both animal models and clinical studies, the specific effect of PTH1-34 for bone fusion after spinal arthrodesis remains to be fully clarified.…”
Section: Pthmentioning
confidence: 99%
“…Perioperative treatment with recombinant human parathyroid hormone (teriparatide/Forteo) has been useful for preoperative augmentation of bone quality, with good outcomes in patients with poor bone mineral density scores. This drug not only has antiresorptive but also osteoinductive properties that quickly re-establish good bone quality in patients requiring major spinal deformity surgery (7)(8)(9)(10)(11)(12).…”
Section: Patient Selectionmentioning
confidence: 99%